Augmentation of Mechanical Properties of Sisal Fiber Concrete - Balasubramanian, M; Selvan.S, Senthil; Panwar.D, Vinod (International Journal of Engineering and Technology, 2018)
The properties of sisal fiber concrete were examined in this investigation. To find out the mechanical properties such as  compressive strength, flexural strength, tensile strength was carried out for the control concretes. The similar mix proportion which was utilized to cast control concrete was used to cast sisal fiber concrete were considered and evaluated with the theoretical values as recommended by IS 456 and BS 8110 standards. For comparison, both conventional and SF concrete have been considered to study.  The mix design for M20, M30 and M40 grade of concrete was finished with four distinct proportions of control concrete in trail and error method as per IS10262 – 2009. Four distinctive aspect ratios, four distinctive dosages of fiber were added to the concrete mix to find out the optimum quantity of fiber and aspect ratio. Mix batches of concrete containing 0.5%, 1%, 1.5%,  2% dosage of fiber in the aspect ratio of 100, 200, 300 and 400 were cast. This study proves that the mechanical and bond properties of both SF concrete and conventional concrete as well.